The Mitogenome Relationships and Phylogeography of Barn Swallows (Hirundo rustica). (25th May 2022) - Lombardo, Gianluca; Rambaldi Migliore, Nicola; Colombo, Giulia; Capodiferro, Marco Rosario; Formenti, Giulio; Caprioli, Manuela; Moroni, Elisabetta; Caporali, Leonardo; Lancioni, Hovirag; Secomandi, Simona; Gallo, Guido Roberto; Costanzo, Alessandra; et al.
Abstract: The barn swallow ( Hirundo rustica ) poses a number of fascinating scientific questions, including the taxonomic status of postulated subspecies. Here, we obtained and assessed the sequence variation of 411 complete mitogenomes, mainly from the European H. r. rustica, but other subspecies as well. In almost every case, we observed subspecies-specific haplogroups, which we employed together with estimated radiation times to postulate a model for the geographical and temporal worldwide spread of the species. The female barn swallow carrying the Hirundo rustica ancestral mitogenome left Africa (or its vicinity) around 280 thousand years ago (kya), and her descendants expanded first into Eurasia and then, at least 51 kya, into the Americas, from where a relatively recent (<20 kya) back migration to Asia took place. The exception to the haplogroup subspecies specificity is represented by the sedentary Levantine H. r. transitiva that extensively shares haplogroup A with the migratory European H. r. rustica and, to a lesser extent, haplogroup B with the Egyptian H. r. savignii . Our data indicate that rustica and transitiva most likely derive from a sedentary Levantine population source that split at the end of the Younger Dryas (YD) (11.7 kya). Since then, however, transitiva received genetic inputs from and admixed with both the closely related rustica and the adjacent savignii . Demographic analyses confirm this species' strong link with climate fluctuations and human activities making it an excellent indicator for monitoring and assessing the impact of current global changes on wildlife.